Vision training and reaction training for improving performance and reducing injury risk in athletes sports vision training - Clark, J.; Betz, B.; Borders. L.; Kuehn-Himmler, A.; Hasselfeld, K.; Divine, J. (Journal of Sports and Performance Vision, 2020)
Visual processing, visual fields, and visual reaction times are essential to the performance of numerous sports and play a role in athletic injuries. Vision training, a process using visual exercises as part of a structured sports conditioning program, can be used to both enhance sports performance and prevent injury by improving neurovisual processing.